2010
DOI: 10.4103/0973-1296.66929
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity evaluation of Xanthorrhoea johnsonii leaf methanolic extract using the Artemia franciscana bioassay

Abstract: The toxicity of Xanthorrhoea johnsonii methanolic leaf extract was investigated using the Artemia franciscana nauplii bioassay. At 24 h, the extract produced an EC50 of 361.0 ± 41.8 μg/ml, indicating that it was substantially more toxic than the pesticide Mevinphos (1346.2 ± 80.1 μg/ml) and approximately 4 fold less toxic than potassium dichromate (87.1 ± 5.2 μg/ml). Whilst potassium dichromate LC50 values remained constant across the 72-h test period, these values decreased for the extract and Mevinphos to si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 15 publications
1
17
0
Order By: Relevance
“…For comparison, the reference toxins potassium dichromate (800 µg/mL) and Mevinphos (2000 µg/mL) were also tested in the bioassay. The potassium dichromate [ Figure 1f] and Mevinphos [ Figure 1g] positive controls both induced the onset of mortality within 24 h of exposure, with 100% mortality induction by 36 h. In agreement with previous reports, [4] the X. johnsonii methanol extract [ Figure 1a] induced apparent morbundity very rapidly. Indeed, 87.8±0.9% apparent morbundity was seen at 12 h, with 100% apparent morbundity at 24 h. Also similar to our previous report was the decrease in apparent morbundity between 36 h and 60 h of exposure, reaching a minimum of 52.1±12.1% by 60 h. A similar trend was evident for the ethyl acetate extract [ Figure 1c] with approximately 100% apparent morbundity recorded at 12 h, and a decrease in apparent morbundity to a minimum of 65.7±10.7% at 60 h of exposure.…”
Section: Quantification Of Toxicitysupporting
confidence: 89%
See 1 more Smart Citation
“…For comparison, the reference toxins potassium dichromate (800 µg/mL) and Mevinphos (2000 µg/mL) were also tested in the bioassay. The potassium dichromate [ Figure 1f] and Mevinphos [ Figure 1g] positive controls both induced the onset of mortality within 24 h of exposure, with 100% mortality induction by 36 h. In agreement with previous reports, [4] the X. johnsonii methanol extract [ Figure 1a] induced apparent morbundity very rapidly. Indeed, 87.8±0.9% apparent morbundity was seen at 12 h, with 100% apparent morbundity at 24 h. Also similar to our previous report was the decrease in apparent morbundity between 36 h and 60 h of exposure, reaching a minimum of 52.1±12.1% by 60 h. A similar trend was evident for the ethyl acetate extract [ Figure 1c] with approximately 100% apparent morbundity recorded at 12 h, and a decrease in apparent morbundity to a minimum of 65.7±10.7% at 60 h of exposure.…”
Section: Quantification Of Toxicitysupporting
confidence: 89%
“…Recent studies from our laboratory tested this hypothesis by examining X. johnsonii leaves for toxicity using the Artemia franciscana nauplii (brine shrimp larvae) lethality bioassay. [4,5] Whilst significant toxicity was detected in methanolic extracts of the leaves of X. johnsonii in those studies, another unexpected bioactivity was also reported. The extract had an apparent anaesthetic effect.…”
Section: Original Articlementioning
confidence: 87%
“…20 Toxicity tests of medicines or plant products should be carried out to see whether they are safe for human application. [21][22][23] This study showed the low dosage (150 mg/kg) with a long period administration for 90 days of KDMLKP, RHKP, and HNKP employing in the present study did not affect body weight gain, food intake, haematological values, and blood biochemistry including BS, BUN, CREA, UA, TP, Alb, Glob, AST, ALT, and ALP. Blood biochemistry including BS, BUN, CREA, UA, TP, Alb, and Glob are reported to involve in renal function.…”
Section: Discussionmentioning
confidence: 77%
“…Toxicity of the P. angustifolia extracts, conventional antibiotics and controls was assessed using a modified Artemia franciscana Kellogg nauplii lethality assay [32,33]. Briefly, 400 μL of artificial seawater containing 40-60 live A. franciscana nauplii was added to each well of a 48-well microtitre plate.…”
Section: Brine-shrimp Lethality Assaymentioning
confidence: 99%